Uniaxial compressive fatigue behavior of ultra-high performance concrete reinforced with super-fine stainless wires. (January 2021) - Dong, Sufen; Wang, Yanlei; Ashour, Ashraf; Han, Baoguo; Ou, Jinping
Highlights: SSWs can remarkably improve compressive fatigue life of concrete at low content. Adding 0.5% SSWs achieves 263% of increase in concrete fatigue energy dissipation. Composite fatigue limit at 50% failure probability reaches 77% of static strength. Addition of SSWs results in dense matrix structure and multiple radial microcrack. SSWs' reinforcing effects cause 74% of increase in concrete fatigue deformation. Abstract: Super-fine stainless wires (SSWs) with micron diameter and large specific surface area can simultaneously strengthen and toughen reactive powder concrete (RPC) at low volume fraction, so SSW reinforced RPC composites have potential for developing infrastructures bearing fatigue load or with aseismic requirements. In this paper, the uniaxial compressive fatigue characteristics of such composites under high stress levels were investigated, and the modification mechanisms of SSWs to RPC were revealed through failure state and microstructure analyses. The results showed that incorporating only 0.5 vol% SSWs into RPC enables the fatigue life and energy dissipation capacity to increase by 252.0% and 262.3%, meanwhile, the fatigue limit strength of composites at the failure probability of 50% reaches up to 76.6% of static uniaxial compressive strength, due to the improvement effect on microstructure compactness, inhibiting effect on flaw initiation, and the ability to convert single main crack into radial multiple micro cracks centered on SSWs. Furthermore, the average maximum fatigue strain and residual strain of composites are improved by 73.7% and 87.2%, respectively, which can be ascribed to the bridging, debonding and being pulled-off effect of SSWs. It can be therefore concluded that the incorporation of SSWs endows RPC with excellent fatigue performance, thus further enlarging the application of composites.